1983
DOI: 10.2190/8g9x-rtfn-f0cd-3dbc
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship with Grandparents: Contact, Importance, Role Conception

Abstract: While studies have considered the importance of the grandparent and grandchild relationship from the perspective of the former, the present study explores the perspective of young adult grandchildren concerning this relationship. Four relationship variables are examined: 1) the amount of contact; b) the assessed adequacy of contact; 3) the importance of the relationship; and 4) the role conception. The results of this study support the position that grandparents remain a significant factor in the lives of youn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
41
1
4

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(50 citation statements)
references
References 11 publications
4
41
1
4
Order By: Relevance
“…Em menor escala apareceram as categorias: não tenho preferência, prefiro a avó paterna, prefiro o avô materno e prefiro o avô paterno (Tabela 5). Estes resultados confirmam a literatura, através dos trabalhos realizados por Matthews & Sprey (1985), Eisenberg (1988), Hoffman (1979/80), Harsthorne & Manaster (1982), os quais demonstraram que a avó materna sobressaiu na preferência dos(as) netos(as). Mas, o que estas pesquisas nos informam também é que, em geral, o avô materno vem em seguida na preferência dos(as) netos(as) e no presente estudo observamos que a avó paterna veio antes do avô materno, continuando com o avô paterno como o menos preferido.…”
Section: Discussão Dos Resultadosunclassified
See 2 more Smart Citations
“…Em menor escala apareceram as categorias: não tenho preferência, prefiro a avó paterna, prefiro o avô materno e prefiro o avô paterno (Tabela 5). Estes resultados confirmam a literatura, através dos trabalhos realizados por Matthews & Sprey (1985), Eisenberg (1988), Hoffman (1979/80), Harsthorne & Manaster (1982), os quais demonstraram que a avó materna sobressaiu na preferência dos(as) netos(as). Mas, o que estas pesquisas nos informam também é que, em geral, o avô materno vem em seguida na preferência dos(as) netos(as) e no presente estudo observamos que a avó paterna veio antes do avô materno, continuando com o avô paterno como o menos preferido.…”
Section: Discussão Dos Resultadosunclassified
“…Em geral, elas revelaram que as expectativas e as atitudes perante os avós, para a maioria dos participantes, foram bastante positivas, tendo sido enfatizado que o relacionamento com eles foi decisivo em suas vidas (Robertson, 1976;Harsthorne & Manaster, 1982;Kennedy, 1989, Matthews & Sprey, 1985Hodgson, 1992). Na pesquisa de Sanders e Trygstad (1993), os universitários referiram-se aos avós como figuras importantes tanto no aspecto social (respeito, influência no próprio comportamento, participação nos acontecimentos da família), como no pessoal (fonte de aprendizagem, senso de perspectiva, ligação emocional).…”
unclassified
See 1 more Smart Citation
“…Even before Smith, researchers with no evolutionary overview had reported that American children feel closer, on average, to their MGMs than to their PGMs (e.g., Kahana and Kahana, 1970;Hoffman, 1980;Hartshorne and Manaster, 1982), and after Smith, studies in several countries have replicated his frequency of contact results (e.g., Eisenberg, 1988;Uhlenberg and Hammill, 1998;Laham et al, 2005), and/or demonstrated other sorts of biased engagement and investment favoring the maternal side (e.g., Eisenberg, 1988;Tyszkowa, 1991;Boon and Brussoni, 1996;Euler and Weitzel, 1996;Salmon, 1999;Dubas, 2001;Chrastil et al, 2006;Pashos and McBurney, 2008;Bishop et al, 2009;Kirchengast and Putz, 2016).…”
Section: Grandmothering In Modern Democraciesmentioning
confidence: 99%
“…However, the investment of relatives in children differs. Asymmetric caregiving structures among grandparents have been well known since the 1970s (e.g., Eisenberg 1988;Euler and Weitzel 1996;Hartshorne and Manaster 1982; Hoffman 1979−80;Littlefield and Rushton 1986). On average, the maternal grandmother provides the most care for grandchildren, followed by the maternal grandfather and…”
mentioning
confidence: 99%